Earnings Management Using Real Activities: Evidence from Nonprofit Hospitals - Eldenburg, Leslie G; Gunny, Katherine A; Hee, Kevin W; Soderstrom, Naomi (The Accounting Review, 2011)
ABSTRACT We extend the literature on earnings management through real operating decisions by providing insight into the types of expenditures (core versus noncore and operating versus non-operating activities) affected by earnings management. We partition a sample of California nonprofit hospitals based on their earnings management incentives. We find that expenditures on non-operating and non-revenue-generating activities appear to decrease in hospitals with incentives to engage in such behavior, while core patient care activities remain unchanged. We also find evidence of earnings management in non-core operational expenses. Second, we analyze real earnings management related to pay-for-performance incentives and find that hospitals with stronger performance incentives exhibit a significant incremental decrease in expenditures. Finally, we examine two different kinds of behavior to discriminate between earnings management and good operational decisions and provide weak evidence to support opportunism rather than good management. Together, these results provide evidence of the use of real operating decisions to manage earnings.